PC4 induces lymphangiogenesis dependent VEGF-C/VEGF-D/VEGFR-3 axis activation in lung adenocarcinoma - Tao, Shaolin (Am J Cancer Res, 2015)
Human transcriptional positive cofactor 4 (PC4) is a novel marker for diagnosis and treatment of advanced human cancers metastasis. In human lung adenocarcinoma, tumor lymphangiogenesis, an important early event, can promotes lymphatic metastasis, while it has been reported that VEGF-C/VEGF-D/VEGFR-3 axis plays an important role in lymphangiogenesis. The proposed study aims to explore whether PC4 correlates with VEGF-C/VEGF-D/VEGFR-3 axis of lymphangiogenesis in the lymph node metastasis during lung adenocarcinoma. Here, small interfering RNA technique was employed to investigate the relationship of PC4 and the VEGF-C/VEGF-D/VEGFR-3 axis in lung adenocarcinoma cell lines as well as tumor xenografts of mice model. And then mRNA and protein levels of PC4, VEGF-C, VEGF-D and VEGFR-3 were analyzed. Moreover, the correlation between PC4 expression and lymphatic vessel density or the rate of metastatsis in vivo was also revealed. Down-regulating PC4 expression resulted in the lower expression of VEGFC, VEGF-D and VEGFR-3 in mRNA and protein levels, and PC4 expression was significantly related with the factor of VEGF-C/VEGF-D/VEGFR-3 axis expression (P<0.05). Meanwhile, high expression level of PC4 was accompanied by the higher density of tumor lymphatic vessels and the rate of metastatsis in vivo (P<0.05). PC4 expression correlated with the levels of VEGF-C, VEGF-D and VEGFR-3 during the development of lymphangiogenesis and lymphatic metastasis in lung adenocarcinoma in vitro and in vivo, which may be a novel marker in the development of lymphangiogenesis and lymphatic metastasis of tumors.